‘Hallberd of Balderdash’ or an attempt at decoding Alexei Chicherin’s construemes (dedicated to the 100th anniversary of their publication) - Svetlana G. Gorbovskaya (Слово.ру: балтийский акцент, 2024)
This paper is the first attempt to interpret the visual 'construemes' by the constructivist poet Alexei N. Chicherin, published in the anthology Mena vsekh (Moscow, 1924). 'Construemes' can be considered the most enigmatic artefacts of the Russian avant-garde. Although 'construemes' can be easily confused with meaningless visual zaum ('the transrational'), Chicherin's actions and the very nature of his personality prevent one from interpreting 'construemes' as actionist endeavours to scandalise or a 'play on nonsense'. Analysis of the poet's treatise Kan-Fun (Moscow, 1926), which required finding the key to deciphering the 'construemes', reveals the positivist nature of Chicherin's visual-phonological exercises. In the treatise, the poet argues for the primacy of the eye and vision. He illustrates synthetic 'signs' or 'pictograms' with the quotidian example of propaganda posters, capable of influencing millions more effectively than words alone. The study emphasises the enigmatic nature of the titles of Chicherin's books, the Nietzschean subtexts of his self-presentation, encrypted allusions to the esoteric and magical tradition of the Tarot, and religious symbolism. Sixteen illustrations help understand Chicherin's logic behind the creation of his four 'construemes', including the most mysterious composition called 'Raman' ('the shortest Kan-Fun Novel in the world'). The structure of this text synthesises the verbal, visual-graphic, acoustic (phonological symbols) and musical (notes) levels. The article also examines Chicherin's proven techniques: the appropriation of the sacred dimension and self-presentation as an actor possessing genuine knowledge and capable of competing alone with the entire literary environment.